2009
DOI: 10.1109/tcomm.2009.08.070288
|View full text |Cite
|
Sign up to set email alerts
|

Power and rate control with outage constraints in CDMA wireless networks

Abstract: A radio power control strategy to achieve maximum throughput for the up-link of CDMA wireless systems with variable spreading factor is investigated. The system model includes slow and fast fading, rake receiver, and multi-access interference caused by users with heterogeneous data sources. The quality of the communication is expressed in terms of outage probability, while the throughput is dened as the sum of the users' transmit rates. The outage probability is accounted for by resorting to a lognormal appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…(12) Note that N d and N v are represented in terms of each other. (9) and (11), can therefore be used to derive explicit expressions…”
Section: Cross-layer Design and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) Note that N d and N v are represented in terms of each other. (9) and (11), can therefore be used to derive explicit expressions…”
Section: Cross-layer Design and Optimizationmentioning
confidence: 99%
“…Typically, this is achieved by employing multi-code (MC)/variable spreading factor (VSF), where transmission rates are adapted to fading-induced channel quality fluctuations. However, the results from [8] and [9] have shown that further adapting the transmission rate to the time-varying MUI levels, can significantly improve effective throughput. Further, most of the previous work on multi-rate CDMA have been implemented based on the BER performance in physical (PHY)-layer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some algorithms minimize total transmission power consumption over a set of discrete available power levels (e.g., [43]). Still other algorithms seek to minimize outage probability of the SIR (e.g., [24,44]). …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on Integer Linear Programming (ILP) for power optimization formulations have been conducted by (e.g., [7,18,24,32,44,46]). Power and rate control outage based under multiple access interference (MAI) and heterogeneous traffic sources have been proposed by [24,44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation